2022
DOI: 10.1101/2022.03.05.483104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of Hydrophobic Interactions of SARS-CoV-2 and MERS-CoV Spike Protein Fusion Peptides Using Single Molecule Force Measurements

Abstract: We address the challenge of understanding how hydrophobic interactions are encoded by fusion peptide sequences within coronavirus (CoV) spike proteins. Within the fusion peptides of SARS-CoV-2 and MERS-CoV, a largely conserved peptide sequence called FP1 (SFIEDLLFNK and SAIEDLLFDK in SARS-2 and MERS, respectively) has been proposed to play a key role in encoding hydrophobic interactions that drive viral-host cell membrane fusion. While a non-polar triad (LLF) is common to both FP1 sequences, and thought to dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 88 publications
(163 reference statements)
0
3
0
Order By: Relevance
“…Intricate details regarding hydrophobic profile as obtained in this research endeavor can play a role in peptide therapeutics. Results here indicate that computational approach for hydrophobic characterization helps in understanding protein folding and related aspects [39,40].…”
Section: Hydrophobic Profile Of Spike Proteins Of Sars-cov-2 and Sars...mentioning
confidence: 77%
See 1 more Smart Citation
“…Intricate details regarding hydrophobic profile as obtained in this research endeavor can play a role in peptide therapeutics. Results here indicate that computational approach for hydrophobic characterization helps in understanding protein folding and related aspects [39,40].…”
Section: Hydrophobic Profile Of Spike Proteins Of Sars-cov-2 and Sars...mentioning
confidence: 77%
“…Leucine and phenylalanine, which are found inside the protein's core, are crucial for structural stability, and these occur most frequently in the whole spike protein when comparing SARS-CoV-2 and SARS-CoV [49]. These variations to the spike protein's amino acids may have an impact on how well the spike protein binds to other proteins during the viral fusion process [39]. Also, Srinivasulu and colleagues as well as Zheng and Song reported that the SARS-CoV-2 and SARS-CoV spike proteins share nearly 73.5% amino acid sequence identity, implying that the remaining 24.5% non-conserved amino acid sequences may be accountable for the antigenic variations between these two proteins which supports the findings for the hydrophobic profile of spike protein of SARS-CoV-2 and SARS-CoV [14,19,38,44], discussed here.…”
Section: Hydrophobic Profile Analysis Of Best Aligned Protein Sequenc...mentioning
confidence: 99%
“…37 The second option suggests a deeper binding mode, as demonstrated previously for the SARS-CoV2 Spike protein fusion loop. 38 Here, subsequent atomic force microscopy (AFM) experiments revealed that the strength of the disassociation of the protein's fusion loop from a hydrophobic surface was 1.91 nN, 39 substantially higher than for Synaptotagmin-1−membrane disassociation. In addition, a recent computational study has shown that class I fusogens have the highest membrane-binding affinities, rationalized by the deep insertion of their hydrophobic fusion loops.…”
Section: ■ Discussionmentioning
confidence: 97%